High Utilization of Humidified Ammonia and Methane in Solid Oxide Fuel Cells: An Experimental Study of Performance and Stability. Issue 12 (17th July 2019) - Stoeckl, Bernhard; Preininger, Michael; Subotić, Vanja; Gaber, Christian; Seidl, Michael; Sommersacher, Peter; Schroettner, Hartmuth; Hochenauer, Christoph
Abstract : Wastewater contains high amounts of unused energy in the form of dissolved ammonia, which can easily be converted into gaseous humidified ammonia via membrane distillation, thus providing a potential fuel for solid oxide fuel cells. This study presents comprehensive investigations of the use of humidified ammonia as the primary fuel component in high-fuel utilization conditions. For these investigations, large planar anode- and electrolyte-supported solid oxide single cells were operated at the respective appropriate temperatures, 800°C and 850°C. Fueled with ammonia, both cells exhibited excellent ammonia conversion ( > 99.5%) in addition to excellent performance output and fuel utilization. In 100 h stability tests performed at 80% fuel utilization, the cells exhibited stable performance, despite scanning electron microscopy analyzes revealing partial impairments to the nickel parts of both cells due to the formation and subsequent decomposition of nickel nitride. This study also demonstrates that methane is a perfect additional fuel component for humidified ammonia streams, as steam supports the internal reforming of methane. Alternating and direct current as well as electrochemical impedance measurements with a variety of ammonia/steam/methane/nitrogen fuel mixtures were used to evaluate the performance potential of the cells, and proved their stability over 48 h in highly polarized conditions.